Caracterização molecular de Rhodococcus equi de potros pela PCR multiplex dos genes da família vap - Monego, Fernanda (2008)
This study evaluated molecular characteristic of Rhodococcus equi isolates obtained from horses and standardized by PCR multiplex assay, which amplifies the vap gene family (vapA, B, C, D, E, F, G e H). One hundred eighty Rhodococcus equi isolates from different sources: healthy horse s feces (112), soil (12), stalls (23) and clinical isolates (33) of horsebreeding farms, were studied. The technique was standardized and confirmed by sequencing of amplified vap gene family controls. Thirty-two (17.8%) R. equi isolates evaluated were positive for vapA gene and carried at least three another vap genes associated. All 147 isolates from equine feces, stalls and soil from horse-breeding farms did not demonstrate any virulence-associated proteins genes. Thirty-two (97.0%) out of 33 clinical equines isolates were positive to multiplex PCR assay for vap gene family and demonstrated six molecular profile, 100% with vapA, vapD and vapG genes, 86.6% vapF, 76,6% vapH, 43.3% vapC, 36.6% vapE and none vapB. The most frequent molecular profile was vap A, D, F, G and H present in 37.5% of strains. Morever, there was no molecular epidemiological pattern for R. equi isolates from each horse-breeding farm studied. Thus this technique allows the identification of eight vap genes family (vapA, B, C, D, E, F, G e H), it is a practical an efficient method of conducting clinical and epidemiological studies on R. equi isolates.